2002
DOI: 10.1007/s001980200003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Calcaneal Trabecular Bone Structure Assessed with High-Resolution MR Imaging in Patients with Kidney Transplantation

Abstract: The purpose of this study was to use high-resolution magnetic resonance (HR-MR) imaging to analyze the trabecular bone structure of the calcaneus in patients before and after renal transplantation and to compare this technique with bone mineral density (BMD) in predicting therapy-induced bone loss and osteoporotic fracture status. HR-MR imaging (voxel size: 0.195 x 0.195 x 1 mm) was performed at 1.5 T with an axial and sagittal orientation in 48 patients after transplantation, 12 patients before renal transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 28 publications
2
40
0
2
Order By: Relevance
“…Grotz et al reported that vertebral deformities were associated with lower trabecular area, lower trabecular diameter, and increased intertrabecular spacing in transplant recipients compared with transplant recipients without vertebral deformities [66]. Link et al reported that transplant recipients had significantly lower MRI measures of BV/TV, Tb.Sp, Tb.Th, and Tb.N compared with controls; [67] however, spine QCT, trabecular BMD, and DXA hip and spine BMD did not differ between transplant recipients and controls. The MRI and QCT measures differed between fracture and nonfracture end-stage renal disease (ESRD) patients; DXA measures did not.…”
Section: Research Applications: Micro-ct and Micro-mrimentioning
confidence: 69%
See 1 more Smart Citation
“…Grotz et al reported that vertebral deformities were associated with lower trabecular area, lower trabecular diameter, and increased intertrabecular spacing in transplant recipients compared with transplant recipients without vertebral deformities [66]. Link et al reported that transplant recipients had significantly lower MRI measures of BV/TV, Tb.Sp, Tb.Th, and Tb.N compared with controls; [67] however, spine QCT, trabecular BMD, and DXA hip and spine BMD did not differ between transplant recipients and controls. The MRI and QCT measures differed between fracture and nonfracture end-stage renal disease (ESRD) patients; DXA measures did not.…”
Section: Research Applications: Micro-ct and Micro-mrimentioning
confidence: 69%
“…BV/TV did not differ significantly in this small sample of hemodialysis patients compared with controls; however, the pattern of lower surface and greater curve voxels suggested deterioration of the trabecular network. Two cross-sectional studies used high-resolution CT [66] or MRI [67] to evaluate trabecular architecture in renal transplant recipients; patients were evaluated months to years after transplantation. Grotz et al reported that vertebral deformities were associated with lower trabecular area, lower trabecular diameter, and increased intertrabecular spacing in transplant recipients compared with transplant recipients without vertebral deformities [66].…”
Section: Research Applications: Micro-ct and Micro-mrimentioning
confidence: 99%
“…HR-pQ CT and high-spatial-resolution MR imaging have allowed noninvasive study of the microstructural determinants of fracture risk in vivo (21)(22)(23). However, HR-pQ CT and high-spatial-resolution MR imaging have been performed only in the distal extremities (14,15,22,24,25) and not in the hip, which is one of the most important fracture sites and a standard BMD assessment site. This is because HR-pQ CT scanners have small imaging bores that can fit only the ankle or wrist and because signal-to-noise ratio limitations arise when MR imaging of deeper anatomy such as the hip is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Since micro-MR imaging does not involve ionizing radiation, it is particularly suited for repeated shortterm evaluation of bone disease in the immediate post-transplantation period. In a cross-sectional study, Link et al (18) reported significant differences in structural measures of trabecular bone in renal transplant recipients and of the calcaneus in control subjects.…”
Section: Study Subjectsmentioning
confidence: 99%